Impacto de los bioinsecticidas en el control del Minador de la Hoja Phyllocnistis citrella Stainton en el cultivo de Tomate. - Arias Vinces, Roberto Antonio (2025)
Since ancient times, there has been a growing interest in finding alternatives to the use of agrochemicals to control harmful organisms. One of them is the use of bioinsecticides to mitigate the problems related to the excessive use of synthetic chemical insecticides. The main objective of this research was to determine the impact of bioinsecticides on the control of the leaf miner Phyllocnistis citrella Stainton in tomato crops. In preparing this document, updated information was collected from scientific articles and virtual libraries, developing it as a non-experimental bibliographical research, through the use of synthesis, analysis, and summary. The conclusions raised indicated that the use of Bacillus thuringiensis is considered as the main biological insecticide used to control the leaf miner Phyllocnistis citrella; the application of conventional pesticides can lead to pest resistance, so it is necessary to apply Neem-based bioinsecticides, due to its high impact on the significant decrease in the population of P. citrella; The efficiency of bioinsecticides has shown a favorable response for the control of P. citrella, especially with the use of entomopathogenic fungi such as Beauveria bassiana and Metarhizium anisopliae; the application of natural extracts has proven to be efficient in the control of P. citrella, due to the insecticidal properties it has to prevent pests and the use of chemical insecticides for the control of P. citrella has a significant environmental impact.